2018
DOI: 10.1590/1678-7757-2017-0199
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periodontal therapy on neopterin and vascular cell adhesion molecule-1 levels in chronic periodontitis patients with and without acute myocardial infarction: a case-control study

Abstract: The presence of neopterin in gingival crevicular fluid (GCF) is a marker for local and acute immune activation, and the presence of vascular cell adhesion molecule (VCAM-1) in GCF is accepted as a marker for chronic vascular inflammation.ObjectivesThis study aimed to evaluate effects of periodontal treatment on GCF levels of neopterin and VCAM-1 in patients with chronic periodontitis (CP) with acute myocardial infarction (AMI) compared with systemically healthy CP patients.Material and methodsSixty subjects (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…Upregulated VCAM-1 can enhance OC activity and recruit further monocytic OC progenitors in a bone metastasis dormancy model (Lu et al, 2011). Besides, VCAM-1 expression has been reported to be associated with periodontal disease severity in patients with chronic periodontitis (Turgut Cankaya et al, 2018). Hence, we arrived at the conclusion that VCAM-1 targeted by miR-101 promotes the growth of OCs as well as other inflammatory factors.…”
Section: Discussionmentioning
confidence: 83%
“…Upregulated VCAM-1 can enhance OC activity and recruit further monocytic OC progenitors in a bone metastasis dormancy model (Lu et al, 2011). Besides, VCAM-1 expression has been reported to be associated with periodontal disease severity in patients with chronic periodontitis (Turgut Cankaya et al, 2018). Hence, we arrived at the conclusion that VCAM-1 targeted by miR-101 promotes the growth of OCs as well as other inflammatory factors.…”
Section: Discussionmentioning
confidence: 83%
“…Several previous studies found significantly higher Np concentrations in the GCF [ 9 , 11 , 12 ] and oral fluid of subjects with periodontitis [ 15 , 30 ]. Periodontal therapy was associated with a decrease in Np levels [ 9 , 11 , 14 , 18 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies found significantly higher Np concentrations in the GCF [ 9 , 11 , 12 ] and oral fluid of subjects with periodontitis [ 15 , 30 ]. Periodontal therapy was associated with a decrease in Np levels [ 9 , 11 , 14 , 18 , 30 ]. In our study, when the Np levels in the study group before periodontal treatment were compared with the control group, only GCF TA and urinary NC were significantly higher in the study group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study by TurgutÇankaya et al in 2018 evaluated the GCF levels of neopterin in chronic periodontitis and acute myocardial infarction before and after periodontal therapy and reported a possible improvement in the efficiency of myocardial infarction treatment after periodontal treatment because of reduction in the infectious load of the body associated with inflamed periodontium. 22…”
Section: Discussionmentioning
confidence: 99%